EKSISTENSI KEBUDAYAAN MASYARAKAT BALI DI DUSUN LUBUK RAYA KECAMATAN KANDIS - Siti Khairiah; Kamaruddin '; Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This thesis the existence of Balinese culture in the village of Lubuk Raya Kecamtan Kandis. As we know the people of Bali are people who have a lot of culture. Balinese culture is always closely associated with religious ceremonies or religious. The purpose of this study is going to know when the early arrival of the Balinese people in the hamlet Lubuk Raya and the other what the culture and customs of the people of Bali are still being used and how they maintain and preserve their culture by the number of people of Bali are very little compared with other communities. This research was conducted with history or historical research methods. Data collected from interviews. When the study began after the seminar proposal until the completion of the last revision of the thesis writer. The results of this study are the people of Bali are located in the hamlet of Lubuk Raya still adhere to their native culture although there are some differences and how they maintain their culture is one way to perform religious ceremonies regularly every Sunday morning.Keywords: existence of Balinese culture.